2007
DOI: 10.2151/sola.2007-031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dust Storm Frequency in Northern China on Fluctuations of Asian Dust Frequency Observed in Japan

Abstract: Relationship between Asian dust frequency observed in Japan (ADF) and dust storm frequency (DSF) in northern China was examined with up-to-date longterm observational data. Possible climatic conditions associated with variations of ADF were also explored. It was found that DSF at stations in Inner Mongolia and its vicinity (IMV) and ADF behaved nearly parallel to each other from the mid 1970s. Significant positive correlation between DSF in IMV and ADF suggests that IMV has a stronger influence on ADF than oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…In regard to the long-term trends of dust storms in the different areas of northern China, previous studies have demonstrated that dust outbreaks in northwestern China have been decreasing since the mid-1980s (Ding et al, 2005;Gong et al, 2006a;Zhang et al, 2006) and have suggested that this tendency is related to decreased Eurasian snow cover and atmospheric baroclinicity (Zhu et al, 2008;Lee et al, 2013), probably associated with global warming. On the other hand, dust outbreaks in the central region of Inner Mongolia and adjacent regions of northeastern China have occurred with increasing frequency since 2000 (Lim and Chun, 2006;Tian et al, 2007;Zhang and Gao, 2007;Zhang et al, 2008), and desertification resulting from drought conditions and anthropogenic factors (e.g. reduced precipitation/soil moisture, degraded surface vegetation, and overgrazing) in these regions has been identified as a major cause of this increased frequency (Lee and Sohn, 2011;Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the long-term trends of dust storms in the different areas of northern China, previous studies have demonstrated that dust outbreaks in northwestern China have been decreasing since the mid-1980s (Ding et al, 2005;Gong et al, 2006a;Zhang et al, 2006) and have suggested that this tendency is related to decreased Eurasian snow cover and atmospheric baroclinicity (Zhu et al, 2008;Lee et al, 2013), probably associated with global warming. On the other hand, dust outbreaks in the central region of Inner Mongolia and adjacent regions of northeastern China have occurred with increasing frequency since 2000 (Lim and Chun, 2006;Tian et al, 2007;Zhang and Gao, 2007;Zhang et al, 2008), and desertification resulting from drought conditions and anthropogenic factors (e.g. reduced precipitation/soil moisture, degraded surface vegetation, and overgrazing) in these regions has been identified as a major cause of this increased frequency (Lee and Sohn, 2011;Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1 in Lin et al, 2006). According to Tian et al (2007), the dust storms observed at stations in Inner Mongolia and its vicinity have a stronger influence on Asian dust observation in Japan (by Japan Meteorological Agency) than do other dust source regions in northern China. The soil degradation in northeastern China, Inner Mongolia, and eastern Mongolia would therefore have the greatest effect on Japan as compared to other western dust source regions.…”
Section: Cross Plotting 90 Sr and 137 Cs For Various Samplesmentioning
confidence: 99%
“…Igarashi et al: Change of the Asian dust source region sources, features of transportation, and related controlling factors Tian et al, 2007). In addition, the possibility of an eastward expansion of the source of Asian dust was suggested by Kurosaki and Mikami (2003) and Lim and Chun (2006) and later confirmed by Kim (2008).…”
mentioning
confidence: 99%
“…In the East Asian region, Asian dust generated in the Chinese and Mongolian deserts and arid regions develops into severe episodes, creating serious health and socio-economic problems. In the early 2000s, judging from the increasing frequency of such episodes in not only the source region (Inner Mongolia and northeastern China) but also in downwind regions, including Korea and Japan (Kurosaki and Mikami 2003;Tian et al 2007;Kim 2008;Lee and Sohn 2011), this situation appeared to be worsening. However, in recent years, it is reported that the frequency of dust storms in China is decreasing (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%